Review of the Fund's Income Position for FY 2011 and FY 2012. (Policy Papers; Policy Paper ;, 2011)
This paper reviews the Fund's income position for FY 2011 and FY 2012. The paper updates projections provided at the FY 2011 midyear review and sets out related proposed decisions for the current and next financial years. A companion paper provides an update on the consolidated medium-term income and expenditure framework.